Pelaku Hukum Ekonomi dan Organisasi dalam Hukum Bisnis dan Dagang Syariah - Rizkita Ayu` Putri; Chindy Kurnia Ningsih; Irmayani Sitorus (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2026)
This study examines the role of economic law actors and business organizations in Indonesia within the framework of national business law and Islamic business and commercial law. The research aims to analyze the legal position, rights, obligations, and responsibilities of various business entities while evaluating their relevance to the development of the digital economy and their compatibility with sharia principles. This study employs a normative legal research method using statutory, conceptual, and comparative approaches. Data were collected through an extensive review of legislation, legal doctrines, scholarly publications, and other relevant legal sources concerning business organizations and Islamic commercial law. The findings indicate that Limited Liability Companies (PT) remain the dominant form of business organization because they provide legal certainty, separate legal personality, and limited liability protection for shareholders. Nevertheless, the rapid growth of digital platforms, technology-based enterprises, and innovative business models has created legal challenges that require more adaptive regulatory frameworks. From the perspective of Islamic business and commercial law, business organizations are considered legitimate provided that their activities comply with the principles of justice, transparency, accountability, mutual consent, and lawful transactions while avoiding prohibited elements such as riba, gharar, and maysir. The novelty of this study lies in integrating the analysis of economic law actors and modern business organizations with Islamic legal principles to provide a more comprehensive perspective on contemporary business regulation in Indonesia. The study concludes that harmonization between national economic law and sharia principles is essential for creating a sustainable, ethical, and legally certain business environment that supports long-term economic development.